Recent Advances in Green Synthesis of TiO₂ Nanoparticles: Mechanisms, and Applications - Devi Lestari; Imas Masriah (Research in Chemical Engineering, 2025)
Green synthesis of titanium dioxide (TiO₂) nanoparticles has emerged as a sustainable alternative to conventional chemical methods, offering environmental benefits while maintaining superior performance characteristics. This comprehensive review examines recent advances in plant-mediated synthesis of TiO₂ nanoparticles, focusing on synthesis mechanisms, structural properties, and diverse applications. Various biological extracts including leaf extracts (Inula viscosa, Aloe vera, Jatropha curcas), flower extracts (Jasminum, Magnolia champaca), fruit peels (Solanum melongena, Citrus sinensis), and agro-industrial wastes have been successfully employed as bio-reductants and stabilizing agents. The synthesis mechanisms involve complex redox reactions mediated by phytochemicals such as polyphenols, flavonoids, terpenoids, and alkaloids, which serve dual roles as reducing agents and capping ligands. Characterization studies reveal that green synthesis predominantly yields anatase phase TiO₂ with particle sizes ranging from 6-400 nm, depending on the plant source and synthesis conditions. The biogenic nanoparticles demonstrate exceptional photocatalytic performance, achieving complete dye degradation (>99%) within 60 minutes under UV irradiation and enhanced visible light activity compared to conventional TiO₂. Noble metal doping (Au, Ag) further improves performance, with Au/TiO₂ nanocomposites showing 2.5 times higher activity than commercial P25 and remarkable hydrogen evolution rates (468 μmol H₂, 9.3% quantum yield). Applications span environmental remediation, renewable energy production, antimicrobial treatments, and advanced technologies including dye-sensitized solar cells, lithium-ion batteries, and corrosion protection coatings. Despite promising results, challenges remain in batch-to-batch variability and large-scale production standardization. This review consolidates current progress and identifies future research directions toward sustainable, high-performance TiO₂ nanomaterials for environmental and energy applications.